Wireless electrostimulation: a new approach in combating infection?. (March 2017) - Kambouris, Manousos E; Markogiannakis, Antonios; Arabatzis, Michael; Manoussopoulos, Yiannis; Kantzanou, Maria; Velegraki, Aristea
Electrostimulation (ES), hitherto successfully employed in wound treatment, has shown potential in antimicrobial applications, suggesting its use as synergistic to or replacement of antibiotics. The differential susceptibility of pathogens and host tissue and organs to various ES modalities might allow selective use against specific infections. The use of ES is cheaper in terms of development/testing, routine application and environmental footprint. If extensive substitution of chemical compounds is achieved, the development of resistance might be reversed through negative selection. A promising setup of ES seems to be the noncontact current transfer, due to low amperage similar to innate bioelectricity, painlessness, simple logistics and low risk for treatment-caused infection.